2014
DOI: 10.2141/jpsa.0130105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combinations of Monochromatic LED Light Color on the Performance and Behavior of Laying Hens

Abstract: The present study evaluated the effect of monochromatic and combinations of light emitting diode light color on the performance and behavior of laying hens. At 12 weeks of age, 600 Hy-line Brown pullets were randomly divided into eight lighting treatments with three replicates of 25 birds in each room. The lightning was set-up as follows; white (W, control; 16 h/d), red (R; 618-635 nm; 16 h/d), green (G; 515-535 nm; 16 h/d), blue (B; 455-470 nm; 16 h/d), red→ green (R→G; 14 h→2 h/d), red→ blue (R→B; 14 h→2 h/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…Furthermore, broiler birds reach market weight by 6 woa and are thus considered juvenile. Nonetheless, Hassan et al (2014) also found that laying hens under red light had better feed conversion, which is in line with the results in our trial, as birds under LED-R produced the same number of eggs while consuming less feed. When comparing feed conversion in layers, it is important to consider environmental housing, as energy expenditure directly relates to the level of activity or thermoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, broiler birds reach market weight by 6 woa and are thus considered juvenile. Nonetheless, Hassan et al (2014) also found that laying hens under red light had better feed conversion, which is in line with the results in our trial, as birds under LED-R produced the same number of eggs while consuming less feed. When comparing feed conversion in layers, it is important to consider environmental housing, as energy expenditure directly relates to the level of activity or thermoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Lighting systems for livestock production, in particular for poultry, are influential for animal health and productivity [66,67]. Diverse lighting systems have been used in the poultry industry.…”
Section: Sustainable Intensification Technologiesmentioning
confidence: 99%
“…Most researchers have focused on the effects of monochromatic LED light colour on the behaviour of hens. Hassan et al (2014) mentioned that higher frequencies of ground pecking, ground scratching, and tail wagging were observed in the red light and these behaviours were less frequent in the blue light [9]. Huber-Eicher et al (2013) indicated that hens under green light spent more time on pecking at objects and had more frequent pecking at conspeci cs compared with red and white light.…”
Section: Introductionmentioning
confidence: 99%